TRADISI BRAHMA YAJÑA DI PASRAMAN SERULING DEWATA DESA BANTAS KECAMATAN SELEMADEG TIMUR KABUPATEN TABANAN - Maheswari, Prasanthy Devi (PANGKAJA: JURNAL AGAMA HINDU, 2020)
Learning Brahma Yajña in Parsaman Seruling Dewata have functions that are historically significant, that is a university of yogi must be preserved, the pragmatic function is the continued to keep organizing activities of pasraman, although in the beginning of its implementation has a constraint at the location of pasraman before, and theological function is the belief that the study of the Vedic scriptures is a concrete manifestation of Brahma Yajña (sacred sacrifice to God). The Brahma Yajña using two methods, the first general method is called method Dasa Dharma, namely: dharmacarita, dharmalìla, dharmagìta, dharma craft, dharma shanty, dharma discourse, dharma yatra, dharmatula, dharma sadhana, dharmavrata (dharmabrata). The two special methods are called Brahma Yajña method itself, namely the method of reading the Catur Vedic and the other complementary sacred literature. The implications of Brahma Yajña's, namely: Brahma Yajña gives way to mankind in achieving liberation (moksha), the expansion of knowledge of the Vedas, the formation of self-control, the increase of sraddha against the Vedic scriptures, be a wiser in the use of the Vedic argument, shaping obedience to the rules, and enhanced the sense peace of life